Effectiveness of Integrating MOOCs in Traditional Classrooms for Undergraduate Students - Israel, Maria Joseph (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The idea of a Massive Open Online Course (MOOC) has attracted a lot of media attention in the last couple of years. MOOCs have been used mostly as stand-alone online courses without credits. However, some researchers, teachers, colleges, and universities have attempted to utilize MOOCs in blended format in traditional classroom settings. This paper reviews some recent experiments in the context of current trends in MOOCs by examining methodologies utilized in blended MOOCs in a face-to-face environment. This paper further discusses the preliminary findings related to its effectiveness of learning outcomes and its impact on students and instructors in blended MOOCs format. The review of blended MOOCs in classrooms assists to form the emerging consensus on integrating MOOCs in conventional classroom settings, while highlighting potential opportunities and challenges one might face when implementing MOOCs in similar or entirely different contexts.